Irritable Brain Caused by Irritable Bowel? A Nationwide Analysis for Irritable Bowel Syndrome and Risk of Bipolar Disorder - Liu, Chia-Jen; Hu, Li-Yu; Yeh, Chiu-Mei; Hu, Yu-Wen; Chen, Pan-Ming; Chen, Tzeng-Ji; Lu, Ti (PLOS ONE, 2015)
Objective We explored the association between IBS and the development of bipolar disorder, and the risk factors for bipolar disorders in patients with IBS. Methods We identified patients who were newly diagnosed with IBS between 2000 and 2010 in the Taiwan National Health Insurance Research Database. We also identified a comparison matched cohort without IBS. The occurrence of new-onset bipolar disorder was evaluated in both cohorts. Results The IBS cohort consisted of 30,796 patients and the comparison cohort consisted of 30,796 matched patients without IBS. The incidence of bipolar disorder (incidence rate ratio, 2.63, 95% confidence interval (CI) 2.10–3.31, P < .001) was higher in the IBS patients than in the matched cohort. Multivariate matched regression models indicated that autoimmune diseases (HR 1.52, 95% CI 1.07–2.17, P = .020), and asthma (HR 1.45, 95% CI 1.08–1.95, P = .013) were independent risk factors for the development of bipolar disorder in the IBS patients. Conclusion IBS may increase the risk of developing subsequent bipolar disorder. Additional prospective studies are required to confirm these findings.